1999
DOI: 10.3758/bf03200737
|View full text |Cite
|
Sign up to set email alerts
|

Web-based administration of a personality questionnaire: Comparison with traditional methods

Abstract: The World-Wide Web holds great promise as a mechanism for questionnaire-based research. But are data from Web-based questionnaires comparable to data from standard paper-and-pencil questionnaires? This study assessed the equivalence of the Ruminative Responses Scale in a Web-based format and in a paper-and-pencil format among introductory psychology, upper-level psychology, and non-psychology students. Internal consistency coefficients were comparable across the groups. The participants in the Web sample repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
2
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(123 citation statements)
references
References 37 publications
1
116
2
4
Order By: Relevance
“…The overall response rate for the GP surveys was low at 47%, markedly lower than that postulated by other authors, 23,24 who describe an expected response rate between 70% and 75%. However, the positive response to our program was consistent with results from previous Australian and UK studies.…”
Section: Gps Are Satisfied With the Pltcmentioning
confidence: 53%
“…The overall response rate for the GP surveys was low at 47%, markedly lower than that postulated by other authors, 23,24 who describe an expected response rate between 70% and 75%. However, the positive response to our program was consistent with results from previous Australian and UK studies.…”
Section: Gps Are Satisfied With the Pltcmentioning
confidence: 53%
“…There are reasons to believe that this effect extends to Webmediated instruments. For example, Stones and Perry (1997) found their respondents willing to disclose highly personal information; Davis (1999) found that WWW respondents reported higher levels of self-focused negative thought than did a sample tested in a classroom setting; and Joinson (1999) found that WWW participants responded to a questionnaire in a less socially desirable fashion. Reasons advanced for this include the anonymity of participants (Hewson et aI., 1996) and the "disinhibited" nature of on-line behavior (e.g., Joinson, 1998).…”
Section: Www-mediated Personality Testsmentioning
confidence: 99%
“…Research conducted via the World Wide Web has the advantage of reaching a large number of potential participants and capturing significant diversity with regard to age and background (Davis, 1999;Krantz & Dalal, 2000;Reips, 2000). Although the conditions under which web-based measures are administered are less controlled than those typical of paper-and-pencil methods, studies employing the same instruments on the web and in person indicate that properly designed web-based versions perform well (Buchanan & Smith, 1999;Davis, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted via the World Wide Web has the advantage of reaching a large number of potential participants and capturing significant diversity with regard to age and background (Davis, 1999;Krantz & Dalal, 2000;Reips, 2000). Although the conditions under which web-based measures are administered are less controlled than those typical of paper-and-pencil methods, studies employing the same instruments on the web and in person indicate that properly designed web-based versions perform well (Buchanan & Smith, 1999;Davis, 1999). Overall, well formulated web-based instruments compare favorably with in person methods (Krantz & Dalal, 2000), with the former possibly having the additional advantage that participants appear to be more forthcoming in computer-mediated surveys, possibly due to greater perceived anonymity (Davis, 1999;Locke & Gilbert, 1995).…”
Section: Introductionmentioning
confidence: 99%